Joint continuity of $K_h C$-functions with values in moore spaces - Maslyuchenko, V. K.; Mykhailyuk, V. V.; Filipchuk, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We introduce a notion of a categorical cliquish mapping and prove that, for each $K_h C$-mapping $f : X × Y → Z$ (here, $X$ is a topological space, $Y$ is a first countable space, and $Z$ is a Moore space) with categorical cliquish horizontal $y$-sections $f_y$ , the sets $C_y (f)$ are residual $G_δ$-sets in $X$ for each $y \in Y.$